Comparison of the percutaneous dilatational tracheostomy with and without flexible bronchoscopy guidance in intensive care units - Özlem Öner; Sinem Dağlı; Mehmet Çağatay Gürkok; Ejder Kamil Öztürk; Begüm Ergan; Volkan Hancı; Ali Necati Gökmen; Erdem Yaka (BMC Anesthesiology)
Abstract Backgrounds The benefit of fiberoptic bronchoscopy (FOB) guidance during percutaneous dilatational tracheostomy (PDT) remains unclear. We aimed to compare PDT performed with and without FOB guidance in terms of procedure duration, number of attempts, and perioperative complications. Methods A total of 103 patients were divided into two groups, and the PDT procedure was performed either with or without FOB guidance. The primary outcome of our study was the duration of the tracheostomy procedure (PDT procedure time) and the number of attempts. The secondary outcome was the major/minor complications that might develop during and after tracheostomy. Results The mean PDT procedure time was 8 (4-14) minutes in the FOB (-) group and 7 (3-14) minutes in the FOB (+) group, with no statistically significant difference between them (p = 0.081). The mean number of PDT attempts was the same in both the FOB (-) and FOB (+) groups, 1 (1-3) (p = 0.079). Hypoxemia/desaturation occurred in 1 (2%) patient in the FOB (-) group and in 1 (1.9%) patient in the FOB (+) group (p = 0.748). Cardiac arrhythmia occurred in 2 (3.9%) patients in the FOB (-) group and in 2 (3.8%) patients in the FOB (+) group (p = 0.684). No cases of pneumothorax or pneumomediastinum were observed in either group (p > 0.999). Conclusion No difference was found between the two groups in terms of procedure duration, number of attempts, and perioperative complications when performing PDT in the intensive care unit with or without fiberoptic bronchoscopy guidance. PDT can be performed effectively and safely in critically ill patients using a standardized approach by an experienced team, with or without bronchoscopy guidance. However, further investigation and advanced studies are needed to evaluate both methods in more detail. Trial registration Retrospectively registered. Clinical trial number was not applicable.